ESSENCE AND CONTENT OF INFORMATIONAL COMPETENCE OF A FUTURE SPORT COACH - Kolyada, M.G.; Bugaeva, T.I.; Donichenko, E.Yu. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to reveal the essence and content of the information competence of the future sports coach. Methods and structure of the study. The paper applies a theoretical analysis of scientific papers on the generalization of the classification features of the structure of information competencies of a sports coach. Results and conclusions. The components of the manifestation of the information competence of a sports coach are shown, which include an understanding of how information and communication technologies (ICT) can support sports and training innovations, as well as the ability to use them and digital tools and equipment to facilitate analytical and sports and training activities in achieving high sports results. Guided by the recommendations of various standards regarding the main ICT innovations, a system of information competencies of the future sports coach has been developed, among the components of which the essences of electronic educational resources, mobile technologies, "smart" sensors and devices of physical culture and sports orientation, virtual and augmented reality, artificial intelligence and knowledge mining systems (Data Mining) in sports and coaching activities. The scheme of the classification structure of the information competencies of the future sports coach is proposed.